STUDI KEPATUHAN WAJIB PAJAK DARI ASPEK PENGETAHUAI\, PERSEPSI, DAN SISTEM ADMINISTRASI - Devi Tri Asih; Kautsar Riza Salman (The Indonesian Accounting Review, 2011)
The low level of tax compliance and tax reform in tax administration system are considered the two important issues. This importonce has become the background of this research. This research is expected to be able to answer what factors can affect the level of tax compliance. The variables used in this study include: lorcwledge of tax, the perception of 'fiscus" and tax administration system implementation. This research is quantitative research that examines empirically the relationship among the voriables, €.9., knowledge about taxes, the perception of 'fiscus" and the implementation of modern tax administration system of tax compliance. The sample in this study as taxpayers arefrom the companies registered in the KPP Gubeng. The selection of respondents was done by using the "convenience sampling". Thefinal conclusions from this research are (1) lcnowledge of tac effect on tac compliance; (2) the perception of "ftscus" does not infiuence the tax compliance, and (3) The implementation of modern tax administration affect tax compliance. Results are expected to provide inputsfor the Directorate General of Taxes that they shouldfocus more on their efforts to improve the tax lvtowledge and tax administration system.